Estimating regional fossil fuel CO2 concentrations from 14CO2 observations: challenges and uncertainties - Maier, Fabian; Levin, Ingeborg; Gachkivskyi, Maksym; Rödenbeck, Christian; Hammer, Samuel (Philosophical transactions of the Royal Society. A, Mathematical, physical and engineering sciences, 2023)
The direct way to estimate the regional fossil fuel CO2 surplus (ΔffCO2) at a station is by measuring the Δ14CO2 depletion compared with a respective background. However, this approach has several challenges, which are (i) the choice of an appropriate Δ14CO2 background, (ii) potential contaminations through nuclear 14CO2 emissions and (iii) masking of ΔffCO2 by 14C-enriched biosphere respiration. Here we evaluate these challenges and estimate potential biases and typical uncertainties of 14C-based ΔffCO2 estimates in Europe. We show that Mace Head (MHD), Ireland, is a representative background station for the Integrated Carbon Observation System (ICOS) atmosphere station network. The mean ΔffCO2 representativeness bias when using the MHD Δ14CO2 background for the whole observation network is of order 0.1 ± 0.3 ppm. At ICOS sites, the median nuclear contamination leads to 25% low-biased ΔffCO2 estimates if not corrected for. The ΔffCO2 masking due to 14C-enriched heterotrophic CO2 respiration can lead to similar ΔffCO2 biases as the nuclear contaminations, especially in summer. Our evaluation of all components contributing to the uncertainty of ΔffCO2 estimates reveals that, due to the small ffCO2 signals at ICOS stations, almost half of the 14C-based ΔffCO2 estimates from integrated samples have an uncertainty that is larger than 50%. - - This article is part of the Theo Murphy meeting issue 'Radiocarbon in the Anthropocene'.